Pengembangan Desa Wisata Alae Sektare dalam Meningkatkan Kesejahtraan Masyarakat - Roni Hidayat (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
The study aim to describe and analyze the development of alae sektare beach tourism village in improving welfare. The research method used in this research is descriptive qualitative method. Field research data collection techniques using observation techniques and interview techniques. The research data analysis technique uses triangulation from Milles and Huberman, namely data reduction, data display and verification. The results of the study indicate that the development of the alae sektare beach tourism village in improving the welfare of the community can be done: first, through the allocation of village funds where village funds managed by the village government are partially allocated to develop the alae sektare beach tourism sector and also improve other facilities Second, the development of community resources. the community is actively involved in the management of alae sektare beach tourism by conducting coaching for the development of community knowledge. third, highlighting local wisdom with the appearance of traditional arts and also serving traditional food to attract visitors. This traditional menu is a superior menu that is in great demand by visitors. The conclusion that the management of the alae sektare beach tourism village through the allocation of village funds is still not optimal so that in the future it is hoped that the village government will prioritize village funds for the development of beach tourism to realize the economic independence of the lantik village community in the srimeulue district